Hydraulic mining operation, K.M. & D. Co., Kougarak River, ca. 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Campbell Hydraulic Elevator at work on John L. Bench Left Limit, Kugarok River, property of K.M. & D. Co. F.H. Nowell, Nome, 5667 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number